RELATIONSHIP BETWEEN RECURRENT LARYNGEAL NERVE (RLN) AND INFERIOR THYROID ARTERY (ITA) IN OUR POPULATION: Recurrent Laryngeal Nerve And Inferior Thyroid Artery - Ahmad, Maqbool; Ashraf, Imran; Sharif, Arslan (Pakistan Armed Forces Medical Journal, 2018)
Objective: To find out the relationship between recurrent laryngeal nerve(s) (RLN) and inferior thyroid artery(ITA) in patients undergoing thyroid surgery in our population.Study Design: Descriptive, cross-sectional study.Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi and Combined Military HospitalRawalpindi from Aug 2008 to Dec 2014.Material; and Methods: One hundred recurrent laryngeal nerves, 50 right and 50 left were studied in 64 patients.All cases of benign goiter, malignant T1, T2 goiter, completion thyroidectomy cases on virgin side were included.Malignant T3, T4 cases, redo surgery, and large multi nodular goiter, cases in which posterior nodules havedisplaced the nerve (s) were excluded from the study. The course of the nerve was dissected in the thyroid vicinityand its relation with the inferior thyroid artery was recorded and photographed. All the data and special pointswere noted by the surgeons themselves in a register in all the cases and photographs were also taken. The data wasentered and analyzed using statistical package for social sciences (SPSS) version 16. A p-value of